Ingenuity Pathway Analysis of Gene Expression Profiles in Distal Nerve Stump following Nerve Injury: Insights into Wallerian Degeneration - Yu, Jun; Gu, Xiaosong; Yi, Sheng (Frontiers in Cellular Neuroscience, 2016)
Nerve injury is a common and difficult clinical problem worldwide with a high disability rate. Different from the central nervous system, the peripheral nervous system is able to regenerate after injury. Wallerian degeneration in the distal nerve stump contributes to the construction of a permissible microenvironment for peripheral nerve regeneration. To gain new molecular insights into Wallerian degeneration, this study aimed to identify differentially expressed genes and elucidate significantly involved pathways and cellular functions in the distal nerve stump following nerve injury. Microarray analysis showed that a few genes were differentially expressed at 0.5 and 1 hour post nerve injury and later on a relatively larger number of genes were up-regulated or down-regulated. Ingenuity pathway analysis indicated that inflammation and immune response, cytokine signaling, cellular growth and movement, as well as tissue development and function were significantly activated following sciatic nerve injury. Notably, a cellular function highly related to nerve regeneration, which is called Nervous System Development and Function, was continuously activated from 4 days until 4 weeks post injury. Our results may provide further understanding of Wallerian degeneration from a genetic perspective, thus aiding the development of potential therapies for peripheral nerve injury.